COVID-19 and the Swedish Labor Market – A Register Perspective - Fredrik W. Andersson; Eskil Wadensjö (Institute of Labor Economics (IZA), 2022)
The pandemic has mainly affected the state of health and mortality, but has also had effects on the economy and the labor market. This article reports what happened to the total number of employees, their distribution by sectors and regions and changes in the number of employees for different groups in 2020 compared with 2019 in Sweden. We do not deal with the development of the number and composition of the self-employed. We also do not go into the development of employees' conditions in terms of wages, working hours and working environment. But we are studying something that is in focus for the general debate: How was the development of the number of employees and their composition in 2020, "the first year of the pandemic"? The main result is that we find large differences in the development for different groups.
Keywords: I15; J15; J21; J23; J61; 330; Swedish labor market; COVID-19; employment; migrants